LAPAROSCOPIC INTERVENTIONS IN LEFT SECTIONS COLON CANCER COMPLICATED BY OBTURATION INTESTINAL OBSTRUCTION - K. G. Kubachev; S. V. Artyukhov (Вестник хирургии имени И.И. Грекова)
On the basis of an analysis of 2200 cases of left sections colon cancer complicated by obturation intestinal obstruction the authors showed the possibility and reasonability of two-step operation performance. The first operation formed unloading part and the second was the radical operation in one hospitalization. Given method allowed improvement of the results and quality of life of the patients.